Economic Growth, Income Inequality, and Poverty in Central Sulawesi - Suparman, Suparman; Muzakir, Muzakir; Wahyuningsih, Wahyuningsih; Tallesang, Mukhtar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study examines the relationship and effect of economic growth with poverty and income inequality in Central Sulawesi Province. The source of data used in this study is secondary data from the Central Statistics Agency (BPS) of Central Sulawesi Province. This study also uses the Granger causality test analysis method to test the relationship between the three variables and then panel data regression is carried out to see the effect of each independent variable on the dependent variable. The data used are panel data on the number of poor people, GRDP (Gross Regional Domestic Product) at Constant Prices 2010, and Gini ratio data by regencies/cities in Central Sulawesi Province during the 2011-2019 period. Based on the empirical findings above, it can be concluded that the variable economic growth (GRDP) has a negative effect on the number of poor people in districts/cities in Central Sulawesi Province. Furthermore, the variable economic growth also has a positive and significant influence on income inequality (GINI), where if there is an increase in economic growth, it will cause an increase in income inequality among people in the local area.